Papillary Thyroid Carcinoma Presenting at Entopic and Ectopic Sites - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Papillary thyroid carcinoma (PTC) mostly occurs within the thyroid gland (entopic site), with its occurrence within an ectopic thyroid tissue being rare comprising less than 1% of all thyroid cancers. The coexistence of PTC in entopic and ectopic sites is even rarer, and differentiating ectopic PTC from a metastatic cervical lymph node may pose a diagnostic conundrum. This report is aimed at highlighting the diagnostic challenges and treatment of this rare condition.